Pengaruh Jumlah Uang Beredar, Suku Bunga Dan Nilai Tukar Terhadap Inflasi Di Indonesia Pada Tahun 2014-2023 - Mei Nia Widyaningrum; Meliza (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The purpose of this study was to determine the effect of money supply, interest rates, and exchange rates on inflation in Indonesia for the period 2014-2023. The type of data in this study uses quantitative data and the data source used is secondary data during the period 2014-2023. Data analysis using multiple linear regression analysis methods. The result that the variable money supply has a positive and significant effect on inflation. The interest rate variable has a positive and insignificant effect on inflation. The exchange rate variable has a negative and significant effect on inflation. For the government to prepare steps in implementing monetary policy related to the problem of money supply, interest rates and exchange rates that can affect inflation.